Case Report: Co-occurring de novo SHANK3 and SRCAP variants in a patient with autoimmune encephalitis and exhibiting Phelan-McDermid syndrome features - Li, Li; Zhang, Jie; Shi, Xiaoyan; Huang, Yaqing; Chang, Xingzhi; Zhang, Liya (Frontiers in Genetics, 2025)
Phelan-McDermid syndrome (PMS) is a rare neurodevelopmental disorder caused by a deletion or variant of SHANK3. Patients with PMS typically present with global developmental delay, delayed or absent speech, intellectual disability, hypotonia, autism spectrum disorder, behavioral abnormalities, and minor specific dysmorphic features. The SRCAP variation is rare and may be associated with chromatin remodeling and neural development. The SRCAP and SHANK3 phenotypes display certain overlapping features, including impaired intellectual and delayed speech development as well as behavioral and psychiatric problems. We report the case of a young male with significant recurrent neuropsychiatric symptoms, developmental regression, and cerebrospinal fluid white blood cell 72/mm3. The diagnosis was consistent with antibody-negative autoimmune encephalitis; the patient improved after immunomodulatory treatment. Whole-exome sequencing identified two de novo pathogenic frameshift variants, one in SHANK3 and the other in SRCAP, with SRCAP being a chimeric variant. Both variants were novel and pathogenic according to the pathogenicity rating provided by the American College of Medical Genetics and Genomics.